2003
DOI: 10.1007/s11661-003-0103-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of globularization of Ti-6Al-4V during static heat treatment

Abstract: The mechanisms controlling static globularization of Ti-6Al-4V after deformation and annealing at 900 ЊC and 955 ЊC were established. Microstructural observations suggested that the process of globularization can be divided into two stages. The first includes microstructural changes during deformation and the initial stages of static heat treatment; the second occurs during prolonged static annealing. The initial stage consists of segmentation of the lamellae via boundary splitting, whereas microstructural coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
116
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(125 citation statements)
references
References 18 publications
7
116
1
1
Order By: Relevance
“…in which d a is the thickness of the a lamella, and m g represents the average slope at the root of the triple point [27]. The coefficient A is given by the equation [5]:…”
Section: Flow Behavior and Kinetics Of Microstructure Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…in which d a is the thickness of the a lamella, and m g represents the average slope at the root of the triple point [27]. The coefficient A is given by the equation [5]:…”
Section: Flow Behavior and Kinetics Of Microstructure Evolutionmentioning
confidence: 99%
“…7d, e) also suggest that minimal termination migration occurred. Such observations can be ascribed to the low temperatures and typical findings that termination migration to complete spheroidization typically requires an order of magnitude more time than platelet fragmentation [27].…”
Section: Flow Behavior and Kinetics Of Microstructure Evolutionmentioning
confidence: 99%
“…The possible mechanisms by which lamellar microstructures globularise and coarsen into a globular α p morphology has been studied by various investigators [3][4][5][6][7][8]. Initial work by Weiss et al identified two different boundary splitting mechanisms by which lamellar microstructures globularise.…”
Section: Introductionmentioning
confidence: 99%
“…The break-up of lamellae by globularization as observed in the HT1 and HT2 conditions was characteristic of recrystallization annealing high in the + phase field (>900 o C) [5]. An increased fraction and size of globular in the HT2 condition may be due to a further annealing cycle; or increased temperature or duration than that experienced in the HT1 condition, resulting in the progression of globularization kinetics [5].…”
Section: Resultsmentioning
confidence: 94%
“…An increased fraction and size of globular in the HT2 condition may be due to a further annealing cycle; or increased temperature or duration than that experienced in the HT1 condition, resulting in the progression of globularization kinetics [5]. Globularization in Ti-6Al-4V has been associated with stress relaxation; due to rearrangement of dislocations which can annihilate as they move through the lattice, reducing dislocation density and therefore internal strain [6].…”
Section: Resultsmentioning
confidence: 99%